Collaborative Governance dalam Penanganan Krisis Air Bersih di Desa Fafinesu B Kecamatan Insana Fafinesu Kabupaten Timor Tengah Utara - Maria Sesilia Kosat; Wilfridus Taus; Yohanes Fritantus (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to describe government cooperation in handling the clean water crisis. With a qualitative descriptive approach, the research uses data collection techniques through interviews, observation and documentation. The results of the analysis relate to handling the water crisis by the government, NGOs and the community, making infiltration wells and greening the area around the springs. Regarding power and coercion, he emphasized that there has not been good cooperation between institutions, but each institution has its own participation in handling the water crisis, such as carrying out traditional rituals, using village funds to manage the water crisis, but there are problems such as, there is no good collaboration, management is still based on secular ego, participation between government, private sector and society is still limited. The crisis shows that every government and non-government institution, and the community, has a way to be involved in managing the drinking water crisis, such as coordinating with various parties, creating joint discussions involving the entire government and community, managing rivers, and cleaning water sources. The conclusion of the research is that there is good cooperation between government and non-government institutions starting from the community, village government, district sub-district through related agencies.